2017
DOI: 10.1186/s11689-017-9197-6
|View full text |Cite
|
Sign up to set email alerts
|

Reduced vagal tone in women with the FMR1 premutation is associated with FMR1 mRNA but not depression or anxiety

Abstract: BackgroundAutonomic dysfunction is implicated in a range of psychological conditions, including depression and anxiety. The fragile X mental retardation-1 (FMR1) premutation is a common genetic mutation that affects ~1:150 women and is associated with psychological vulnerability. This study examined cardiac indicators of autonomic function among women with the FMR1 premutation and control women as potential biomarkers for psychological risk that may be linked to FMR1.MethodsBaseline inter-beat interval and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 153 publications
1
16
0
Order By: Relevance
“…Using a rating scale that has been shown to be sensitive to the BAP in family studies of autism spectrum disorder, we indexed BAP features in the FMR1 premutation and found no association with poor eye contact. In another study including an overlapping sample, Klusek et al (2017) also documented an unexpected decoupling between pragmatic language deficits (a primary feature of the BAP) and attention to eye gaze indexed via an experimental eye tracking paradigm. Taken together, these studies demonstrate that atypical use of eye gaze in the FMR1 premutation is not associated with the BAP, as suggested by evidence gathered across a combination of experimental, direct-observation, and informant- and self-report measures.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Using a rating scale that has been shown to be sensitive to the BAP in family studies of autism spectrum disorder, we indexed BAP features in the FMR1 premutation and found no association with poor eye contact. In another study including an overlapping sample, Klusek et al (2017) also documented an unexpected decoupling between pragmatic language deficits (a primary feature of the BAP) and attention to eye gaze indexed via an experimental eye tracking paradigm. Taken together, these studies demonstrate that atypical use of eye gaze in the FMR1 premutation is not associated with the BAP, as suggested by evidence gathered across a combination of experimental, direct-observation, and informant- and self-report measures.…”
Section: Discussionmentioning
confidence: 85%
“…Participants included 38 women with the FMR1 premutation and 27 neurotypical control women who were participating in a larger study on communication profiles in the FMR1 premutation, which has been described previously (e.g., Klusek et al, 2017). Women with the FMR1 premutation were recruited through their children who were participating in larger developmental studies of fragile X syndrome or the FMR1 premutation, or from the local community by word of mouth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Autonomic dysfunction is a common problem in the premutation carriers especially with FXTAS and it usually precedes diagnosis of FXTAS ( Jacquemont et al, 2003 , 2004 ; Pugliese et al, 2004 ; Leehey, 2009 ; Hagerman and Hagerman, 2013 ). In non-FXTAS carriers, a study found that the premutation females had reduced vagal tone which reflects impaired parasympathetic response ( Klusek et al, 2017 ). In terms of cardiovascular disorders, the clinical presentation of autonomic dysfunction includes episodic hypotension ( Pugliese et al, 2004 ; Greco et al, 2006 ; Gokden et al, 2009 ; Hagerman and Hagerman, 2013 ) and hypertension ( Jacquemont et al, 2003 ; Coffey et al, 2008 ; Chonchaiya et al, 2010 ; Hamlin et al, 2012 ).…”
Section: Case Presentationmentioning
confidence: 99%
“…Children with the premutation usually have normal intellectual abilities but approximately 20% are diagnosed with developmental problems or autism spectrum disorder (ASD), which are part of the spectrum of fragile X disorders (FXSD) (Farzin et al, 2006; Lozano et al, 2014). Psychiatric problems such as anxiety, ADHD and/or depression are present in approximately 50% of children and adults with the premutation (Farzin et al, 2006; Bourgeois et al, 2011; Cordeiro et al, 2015; Klusek et al, 2017).…”
Section: Introductionmentioning
confidence: 99%